The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/plankt/fbh171
|View full text |Cite
|
Sign up to set email alerts
|

In situ filtration responses of Daphnia galeata to changes in food quality

Abstract: In the stoichiometric study of phyto-zooplankton interactions, a controversy exists about how Daphnia species regulate their feeding rate when submitted to low-quality food (i.e. high dietary carbon:phosphorus [C:P] ratio). In this study, we gathered data over 3 years on in situ clearance rates of a Daphnia galeata population, by conducting grazing experiments from April 1998 to October 2000 in the Esch-sur-Su ˆre reservoir (Grand-Duchy of Luxembourg). Observed clearance rates (2.5-13.5 mL individual -1 day -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
2
23
1
Order By: Relevance
“…Furthermore, our ingestion rate experiments show changes in foraging rate can operate very quickly. Our ingestion rate experiments are consistent with previous results from Sterner and Smith (1993) and Vandonk and Hessen (1993), but we must point out that Plath and Boersma (2001) and Darchambeau and Thys (2005) found that individual Daphnia also increased their ingestion rate when exposed to poor food quality. One explanation for the differences among ingestion studies could be accounted for by different acclimation procedures reflecting internal stimuli for foraging (e.g., Plath 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our ingestion rate experiments show changes in foraging rate can operate very quickly. Our ingestion rate experiments are consistent with previous results from Sterner and Smith (1993) and Vandonk and Hessen (1993), but we must point out that Plath and Boersma (2001) and Darchambeau and Thys (2005) found that individual Daphnia also increased their ingestion rate when exposed to poor food quality. One explanation for the differences among ingestion studies could be accounted for by different acclimation procedures reflecting internal stimuli for foraging (e.g., Plath 1998).…”
Section: Discussionsupporting
confidence: 92%
“…One explanation for the differences among ingestion studies could be accounted for by different acclimation procedures reflecting internal stimuli for foraging (e.g., Plath 1998). Experiments have shown that individuals acclimated under poor food quality conditions respond by accelerating feeding when presented with high-quality food, whereas individuals not acclimated behave differently (Plath and Boersma 2001;Darchambeau and Thys 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A complete review of the different expected responses has been presented by Mitra et al (2007). For instance, when confronted with poor food quality, zooplankton can increase their ingestion rate (Plath and Boersma, 2001;Darchambeau and Thys, 2005), or decrease it as the food can become deleterious (Flynn and Davidson, 1993). Accounting for the complexities of these different types of behavior has not been implemented within PISCES as this would require a model with flexible stoichiometry.…”
Section: O Aumont Et Al: a Description Of Pisces-v2mentioning
confidence: 99%
“…However, organisms may increase their fitness using this excess of C for other purposes, such as storage, structure and defence (Hessen and Anderson, 2008). Recent studies with phosphorus (P)-limited Daphnia showed adjustments in ingestion rate (Darchambeau and Thys, 2005) and assimilation efficiency of (excess) C and P (DeMott et al, 1998). Furthermore, daphnids may compensate for poor food quality by increasing C excretion (He and Wang, 2008) and respiration (Darchambeau et al, 2003;Jensen and Hessen, 2007), which depends on acclimation time (Lukas and Wacker, 2014).…”
Section: Introductionmentioning
confidence: 99%